2014
DOI: 10.1111/aor.12391
|View full text |Cite
|
Sign up to set email alerts
|

An Environment-Adaptive Management Algorithm for Hearing-Support Devices Incorporating Listening Situation and Noise Type Classifiers

Abstract: In order to provide more consistent sound intelligibility for the hearing-impaired person, regardless of environment, it is necessary to adjust the setting of the hearing-support (HS) device to accommodate various environmental circumstances. In this study, a fully automatic HS device management algorithm that can adapt to various environmental situations is proposed; it is composed of a listening-situation classifier, a noise-type classifier, an adaptive noise-reduction algorithm, and a management algorithm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A maximum flow velocity of 0.94 m/s was observed at the region downstream of the percutaneous valve at the superior vena cava (SVC). Maximum RSS value of 2076.1 dynes/cm was observed downstream of the valve at the inferior vena cava during the deceleration phase while maximum TKE measured was 572.6 J/m at the upstream of the valve in the SVC during the peak flow phase. While these values appear high, they are significantly lower than those reported in prosthetic mitral and aortic valves.…”
Section: Valves and Vascularmentioning
confidence: 90%
See 1 more Smart Citation
“…A maximum flow velocity of 0.94 m/s was observed at the region downstream of the percutaneous valve at the superior vena cava (SVC). Maximum RSS value of 2076.1 dynes/cm was observed downstream of the valve at the inferior vena cava during the deceleration phase while maximum TKE measured was 572.6 J/m at the upstream of the valve in the SVC during the peak flow phase. While these values appear high, they are significantly lower than those reported in prosthetic mitral and aortic valves.…”
Section: Valves and Vascularmentioning
confidence: 90%
“…Sunhyun Yook et al of Hanyang University, Seoul, Korea investigated a fully automatic hearing‐support (HS) device management algorithm that can adapt to various environmental situations. Experimental results demonstrated that the implemented algorithms can classify both listening situations and ambient noise type situations with high accuracies.…”
Section: Auditory Supportmentioning
confidence: 99%
“…First, during the subjective evaluations, we considered only one user-controllable noise reduction algorithm: β -adjustable beamforming. However, in commercial devices, additional algorithms may be required to achieve environment-adaptive adjustment, such as single-microphone-based noise-reduction algorithms using spectral subtraction and Wiener filtering [ 17 , 22 ]. To modify the currently implemented algorithm to have a more conventional hearing aid algorithm structure, it is necessary to include additional user-controllable algorithms, such as single-microphone-based noise-reduction, to better reflect users’ personal preferences for various degrees of ambient noise suppression and speech distortion.…”
Section: Discussionmentioning
confidence: 99%
“…The following assumptions were made for simplification: (1) The device contains two user-adjustable algorithms—beamforming, which adjusts the DNS using the β value, and an output volume adjustment, which adjusts the total output volume of the device using AMP; (2) The wide dynamic-range compression is always active and its channel gains are fixed at purchase; (3) Beamforming is enabled only in speech-in-noise situations and disabled in speech-only and noise-only situations; and (4) The ISL is limited to a 45–90 dB of sound pressure level (dB SPL) range, considering the normal, everyday use presented by Chalupper et al [ 4 ] and Walden et al [ 15 ]. In this study, we used the differential microphone array algorithm suggested by Teutsch and Elko [ 16 ] as the beamforming, and the neural network-based LS classifier suggested by Yook et al [ 17 ] that was slightly modified as follows: (1) Additional amplification in front of the classifier to ensure the proper ISL for stable classification performance and (2) Among the four situations classified in the original LS classifier, only three situations—speech-only, noise-only, and speech-in-noise—were enabled (i.e., music-only was disabled).…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative, it was implemented to update the value of Thr whenever the voice activity detector does not detect the speech signal for approximately 2 s. However, in this case, when the intensity and the type of environmental noises change drastically while the speech signal enters consistently, the value of Thr cannot be adjusted timely to the proper level and as a result, the localization accuracy and intelligibility of the speech signal may decrease. To overcome this problem, in future studies, more elaborated sound source separation or sound classification algorithms, such as independent component analysis or support vector machine , should be added to the current algorithm to adaptively adjust the value of Thr in accordance with the variations in environmental circumstances.…”
Section: Discussionmentioning
confidence: 99%